Emerging Topics in Vaccine Therapeutics for Adolescents and Adults: An Update for Immunizing Pharmacists. (April 2020) - Fava, Joseph P.; Stewart, Brittany; Dudzinski, Kathryn M.; Baker, Michelle; Volino, Lucio
Vaccine therapeutics and the practice of immunization provision are ever-changing. As pharmacy-based immunization services continue to flourish in the United States, more and more patients are requesting both routine and travel vaccines in community pharmacies. However, vaccine recommendations from the Centers for Disease Control and Prevention/Advisory Committee on Immunization Practices (CDC/ACIP) can sometimes differ from product-specific US Food and Drug Administration (FDA)-indicated uses. In addition, changes in vaccine schedules, product availability, and disease outbreaks can present immunizing pharmacists with scenarios requiring a high level of clinical judgment. Thus, it is of paramount importance that all immunizing pharmacists maintain competency in the most recent evidence in vaccine therapeutics, as well as practice standards for vaccine provision and administration. This review provides an update of the most recent literature surrounding emerging topics in adolescent and adult immunizations—highlighting influential studies and recent developments in the prevention of herpes zoster, human papillomavirus (HPV), measles, mumps, rubella (MMR), meningococcal disease, tetanus, diphtheria, and pertussis. Key concepts discussed include the emergence of the new recombinant zoster vaccine (RZV), meningococcal vaccine product selection, MMR revaccination during disease outbreaks, tetanus vaccine product selection, and duration of pertussis immunity with vaccination.